The Characteristics and Distribution of Nerve Plexuses in the Dartos Fascia From Concealed Penis Children - Huang, WenFang; Tang, DaXing; Gu, WeiZhong (Frontiers in Pediatrics, 2021)
The purpose of this study is to analyze the nerve plexus distribution in dartos fascia of concealed penis (CP). A total of 28 CP patients met ASA categories I and II were included, with median age of 3.5 years (8 months−5 years). During the surgery, tissue samples of dartos fascia at points 3, 6, 9, and 12 o'clock of the penile shaft were collected. Standard hematoxylin and eosin (H&E) staining and S-100 immunohistochemical staining were used to analyze the nerve plexus distribution among different positions. The number of nerve plexuses in superficial fascia collected at the 6 o'clock position of the penile shaft was the most abundant among four positions (median 7.25, range 1–24). The abundant nerve plexuses in the dartos fascia of CP patients, especially at the 6 o'clock position, indicate that the surgery on the preputial frenulum should avoid damage to the dartos fascia, as it might be related to maintain the erection and sexual function in adolescence.